How big is big and how small is small: the sizes of everything and why - Smith, Timothy Paul (Oxford University Press, 2013)
This book is about how big is the universe and how small are quarks, and what are the sizes of dozens of things between these two extremes. It describes the sizes of atoms and planets, quarks and galaxies, cells and sequoias. It is a romp through forty-five orders of magnitude from the smallest sub-nuclear particles we have measured, to the edge of the observed universe. It also looks at time, from the epic age of the cosmos to the fleeting lifetimes of ethereal particles. It is a narrative that trips its way from stellar magnitudes to the clocks on GPS satellites, from the nearly logarithmic scales of a piano keyboard through a system of numbers invented by Archimedes and on to the measurement of the size of an atom --